2000
DOI: 10.1093/jn/130.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Implanted Tumor Growth Is Suppressed and Survival Is Prolonged in Sixty Percent of Food-Restricted Mice

Abstract: To examine the effect of food restriction on immune functions in the tumor-bearing state, mice were divided into a control group (fed 5.0 g diet/d; 71 kJ/d) and a 60% food-restricted group (fed 3.0 g diet/d; 43 kJ/d) at 8-wk of age, and 4 wk later, L1210 tumor cells were inoculated intradermally. In the food-restricted mice, tumor growth was significantly suppressed, and mean survival time after the tumor inoculation was prolonged (P < 0.05). The plasma concentrations of two antitumor cytokines, interferon-gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…It has been well established that CR can exert positive effects upon the life span and certain age-related diseases (2,8,14,39,40,43,53,54,71,76,79). This study demonstrated that a period of CR can attenuate sickness behavior following LPS administration.…”
Section: Perspectives and Significancesupporting
confidence: 50%
See 3 more Smart Citations
“…It has been well established that CR can exert positive effects upon the life span and certain age-related diseases (2,8,14,39,40,43,53,54,71,76,79). This study demonstrated that a period of CR can attenuate sickness behavior following LPS administration.…”
Section: Perspectives and Significancesupporting
confidence: 50%
“…fever; suppressor of cytokine signaling 3; cyclooxygenase-2; microsomal prostaglandin E synthase-1; leptin CALORIE RESTRICTION (CR), a dietary regimen low in calories, while avoiding malnutrition, is the only manipulation that has consistently been shown to extend the mean and maximum life span in a range of species (2,42,71,76). In addition to an increase in life span, CR attenuates the normal immunosenscence seen with age (52), along with reducing the occurrence of other age-related diseases (14,39,43,53,54,79).It has been postulated that the mechanism by which CR extends the mean and maximum life span is by reducing oxidative stress caused by unregulated increases in reactive oxygen species (3,19,31,42,69), as well as by limiting the age-related increase in basal pro-inflammatory cytokine levels (73). One possible mechanism by which CR exerts its antiinflammatory effect are glucocorticoids, which are increased after CR (33, 47) and act to increase the transcription of anti-inflammatory cytokines and decrease the transcription of proinflammatory cytokines (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of 14 experimental studies found that energy restriction resulted in a 55% reduction in spontaneous tumors in laboratory mice [7]. Calorie restriction inhibited induced mammary tumors in mice [8] and suppressed implanted tumor growth and prolonged survival in energy restricted mice [9]. Among Swedish women who had been hospitalized for anorexia nervosa (definitely lower caloric intake, but not adequate nutrition) prior to age 40, there was a 23% lower incidence of breast cancer for nulliparous women and a 76% lower incidence for parous women [10].…”
Section: Reviewmentioning
confidence: 99%